Relationship between peer conformity and reproductive health maintenance behaviours among early adolescent girls in Islamic boarding schools - Peni Perdani Juliningrum; Lantin Sulistyorini; Layinatul Qoriah; Ira Rahmawati; Nuning Dwi Merina (PAGEPress Publications, 2024)
Reproductive health problems are often experienced by early adolescents who live in Islamic boarding schools because Islamic boarding schools have a higher population density and interpersonal contact than other schools. In the early adolescent years, there is a tendency in terms of a solid urge to behave like peers, so conformity quickly occurs when adolescents adopt reproductive health care behaviours. This study aimed to determine the relationship between peer conformity and reproductive health maintenance behaviour of early adolescent girls at Islamic boarding schools. This study used a correlational research design with a cross-sectional approach and a purposive sampling technique conducted on 165 early adolescents. The analytical method used for this study was univariate and bivariate analysis tests, in bivariate tests using the Pearson test processed with the Statistical Package for Social Sciences (SPSS) program. The analysis showed that all early adolescents (100%) had a history of vaginal discharge. The results of the bivariate test showed a value of p=0.0001. The level of reproductive health maintenance behaviour is determined by the extent to which conformity occurs in adolescents. Conformity that occurs can affect and change one's perceptions and behaviour.